Glial amplification of synaptic signals. (16th February 2021) - Beppu, Kaoru; Kubo, Naoko; Matsui, Ko
Abstract : Key points: Recent studies have repeatedly demonstrated the cross‐talk of heterogeneous signals between neuronal and glial circuits. Here, we investigated the mechanism and the influence of physiological interactions between neurons and glia in the cerebellum. We found that the cerebellar astrocytes, Bergmann glial cells, react to exogenously applied glutamate, glutamate transporter substrate (d ‐aspartate) and synaptically released glutamate. In response, the Bergmann glial cells release glutamate through volume‐regulated anion channels. It is generally assumed that all of the postsynaptic current is mediated by presynaptically released glutamate. However, we showed that a part of the postsynaptic current is mediated by glutamate released from Bergmann glial cells. Optogenetic manipulation of Bergmann glial state with archaerhodpsin‐T or channelrhodopsin‐2 reduced or augmented the amount of glial glutamate release, respectively. Our data indicate that glutamate‐induced glutamate release in Bergmann glia serves as an effective amplifier of excitatory information processing in the brain. Abstract: Transmitter released from presynaptic neurons has been considered to be the sole generator of postsynaptic excitatory signals. However, astrocytes of the glial cell population have also been shown to release transmitter that can react on postsynaptic receptors. Therefore, we investigated whether astrocytes take part in generation of at least a part of the synaptic current. In this study, mice cerebellar acute slices were prepared and whole cell patch clamp recordings were performed. We found that Bergmann glial cells (BGs), a type of astrocyte in the cerebellum, reacts to a glutamate transporter substrate, d ‐aspartate (d ‐Asp) and an anion conductance is generated and glutamate is released from the BGs. Glutamate release was attenuated or augmented by modulating the state of BGs with activation of light‐sensitive proteins, archaerhodopsin‐T (ArchT) or channelrhodopsin‐2 (ChR2) expressed on BGs, respectively. Glutamate release appears to be mediated by anion channels that can be blocked by a volume‐regulated anion channel‐specific blocker. Synaptic response to a train of parallel fibre stimulation was recorded from Purkinje cells. The latter part of the response was also attenuated or augmented by glial modulation with ArchT or ChR2, respectively. Thus, BGs effectively function as an excitatory signal amplifier, and a part of the 'synaptic' current is actually mediated by glutamate released from BGs. These data show that the state of BGs have potential for having direct and fundamental consequences on the functioning of information processing in the brain. Key points: Recent studies have repeatedly demonstrated the cross‐talk of heterogeneous signals between neuronal and glial circuits. Here, we investigated the mechanism and the influence of physiological interactions between neurons and glia in the cerebellum. We found that the cerebellar astrocytes, Bergmann glial cells, react to exogenously applied glutamate, glutamate transporter substrate (d ‐aspartate) and synaptically released glutamate. In response, the Bergmann glial cells release glutamate through volume‐regulated anion channels. It is generally assumed that all of the postsynaptic current is mediated by presynaptically released glutamate. However, we showed that a part of the postsynaptic current is mediated by glutamate released from Bergmann glial cells. Optogenetic manipulation of Bergmann glial state with archaerhodpsin‐T or channelrhodopsin‐2 reduced or augmented the amount of glial glutamate release, respectively. Our data indicate that glutamate‐induced glutamate release in Bergmann glia serves as an effective amplifier of excitatory information processing in the brain.